A Systematic Literature Review of Tour Guide Performance - Marceilla Suryana (Politeknik Negeri Bandung, 2022)
The performance of tour guides has come to the attention of many researchers, as part of the disclosure of the phenomenon of prestigious professions in the tourism industry. As an important part of the tourism cycle, the profession of a tour guide has a major influence on tourist behavior and the development of tourist destinations. Using the Systematic Literature Review approach, this article reviews previous research that has been published in reputable journals with various backgrounds of locations and phenomena. This literature review study has provided an overview of the factors supporting the performance of tour guides, namely in the aspects of soft-skills and hard-skills, in the form of communication, managerial skills and leadership. It also explained the impact of the performance of tour guides that have been found to be related to tourist satisfaction, tourist experience, behavior in the destination and the desire to revisit.